2009
DOI: 10.3161/00159301ff2009.52.2.157
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the most troublesome mosquito species (Diptera: Culicidae) in Poland

Abstract: Twelve of the 47 Polish mosquito species can pose serious health problems to man or at least heavy nuisance. They fly from breeding sites (where huge numbers can be produced) into houses and/or farm buildings transmitting severe human and animal diseases. A edes species occur along river valleys and their larvae can breed in different pools situated in a variety of environments. C ulex pipiens, especially its form m olestus and C uliseta annulata can breed in natural and artificial ponds, even in heavily pollu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Mosquito species collected in the present study have been already reported in Poland 13,29,37,38 . We found the same dominant species as in the previous study based on females collected from the periphery of mixed birch-oak and riparian forests, near the same collection area 13 .…”
Section: Discussionmentioning
confidence: 53%
“…Mosquito species collected in the present study have been already reported in Poland 13,29,37,38 . We found the same dominant species as in the previous study based on females collected from the periphery of mixed birch-oak and riparian forests, near the same collection area 13 .…”
Section: Discussionmentioning
confidence: 53%
“…All mosquito species collected in this study have been reported in Poland previously [ 95 – 97 ]. A significant relationship was noted between average air temperature and dominant mosquito species.…”
Section: Discussionmentioning
confidence: 99%
“…Original articles on the occurrence of mosquitoes in Poland published after 2000 come from 15 out of 16 voivodeships (Figure 1, Tables 1-3) and concern mostly data from urban areas, including Wrocław [5,10,[14][15][16][17][18][19][20], Gdańsk, Gdynia, Sopot [21], Krynica Morska [22], Warsaw [23], Poznań [24], and Świnoujście [25]. Additionally, based on literature data, a review of species occurring in five Polish towns (Szczecin, Świnoujście, Gdańsk, Warszawa, Wrocław) was published [26].…”
Section: Current Knowledgementioning
confidence: 99%
“…The previous checklist of mosquito species occurring in Poland was published at the end of the 20th century by Kubica-Biernat [4], who listed in her publication 47 mosquito species reported from 223 identifiable sites in Poland. The same list of 47 species was also given by Wegner in 2007 [5].…”
Section: Introductionmentioning
confidence: 99%